Antibiotic resistance and virulence profile of Klebsiella pneumoniae isolated from wild Sumatran Orangutans (Pongo abelii) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Orangutans (Pongo abelii), as endemic primates of Indonesia, are characterized by a predominantly arboreal lifestyle. Klebsiella pneumoniae (K. pneumonia) and other Gram-negative bacteria are present in the Indigenous flora of many mammals, including orangutans. This study aimed to investigate the antibiotic resistance and virulence profile of K. pneumonia isolated from wild Sumatran orangutans. Materials and Methods: This study investigated 10 fecal samples from wild Sumatran orangutans from the Gunung Leuser National Park, Aceh, Indonesia. Biochemical and molecular identification of K. pneumoniae using the RNA polymerase subunit b gene and detection of virulence-associated genes. In addition, molecular detection of antibiotic resistance genes was performed to characterize the resistance mechanisms in the isolates. Results: K. pneumonia was detected in 6 out of 10 fecal samples from wild Sumatran orangutans. The virulence genes mrkD and entB were detected in all (100%) of the isolates, whereas wabG was identified in 83.33% of the strains. Antibiotic susceptibility testing against K. pneumoniae revealed that three isolates were susceptible to streptomycin (S) and nalidixic acid (NA), while all six isolates were susceptible to chloramphenicol and ciprofloxacin. One isolate demonstrated intermediate resistance to NA, while the remaining two exhibited intermediate resistance to S. Six isolates were resistant to ampicillin, tetracycline, and erythromycin, indicating multidrug resistance. Furthermore, antibiotic resistance genes were detected in the isolates with the following prevalence: blaTEM gene (six isolates; 100%), blaSHV (six isolates; 100%), blaCTX-M gene (four isolates; 66.67%), and tetA gene (four isolates; 66.67%). Conclusion: This study revealed the virulence and resistance profile of K. pneumoniae bacterium isolated from wild Sumatran orangutans, which is essential for formulating effective conservation and healthcare strategies. J. Adv. Vet. Anim. Res., 11(4): 1066–1075, December 2024http://doi.org/10.5455/javar.2024.k858